Development Of A Subscale Aircraft For Flutter Test Platform - Tan, Chun Khuen (Universiti Sains Malaysia, 2019)
The interest in building High Altitude Long Endurance (HALE) aircraft are increasing rapidly recently due to its potential benefits on military and commercial usage. However, flutter is always an aeroelasticity issue as these aircraft usually has long, thin and high aspect ratio wing. Thus, it is helpful to develop a subscale aircraft with flutter test capability to investigate the effect of aerodynamic, inertia and elastic forces that act on the flexible wing. In this project, a low-cost, university-level platform is designed and developed. The design was being made to achieve the objectives of this project. Thus, its flight performance in terms of aerodynamics, stability and control, total weight and instrumentations were achieved by using XFLR5, Excel, Arduino and SolidWorks. Next, the aircraft was fabricated with Expanded PolyProplyene (EPP) foam and Depron Extruded Polystyrene (XPS) foam according to the design. Then, a total of 6 flight tests were done, and it took off successfully 3 times. Improvements were being made to initiate flutter. However, flutter was failed to be initiated as the stiffness of the wing is difficult to be tailored. Due to some accidents, the flight test was being put to a stop and Ground Vibration Test (GVT) was being carried out instead. From the GVT, the natural bending and pitching frequencies of the original wing and modified wing are 3.745 Hz, 84.28 Hz, 6.193 Hz and 118.1 Hz respectively. For the empennage’s horizontal and vertical stabiliser, the natural bending frequencies are 8.324 Hz and 7.643 Hz respectively.